DIGITAL MULTIPLEXER - FUJIO HIROYUKI (1992)
PURPOSE:To improve the transmission efficiency at data transmission by generating a multiplexed flag pattern for frame synchronization from a flag pattern of a transmission data of each channel. CONSTITUTION:HDLC data parts 6a-6c of a transmission data inputted from each of channels 1a-1c at a sender side are subject to time division multiplex at a multiplexer circuit 2a. In this case, flag patterns 7a-7c of each transmission data are subject to time division multiplex for each bit by the multiplexer circuit 2a. An HDLC flag pattern generated in this way is outputted as a multiplexed flag pattern 9 of a multiplexed frame 8.